2019
DOI: 10.1177/0969733019845124
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards gossip and patient privacy among paediatric nurses

Abstract: Background: Nurses providing 24-h care for the primary caregiver role have a number of significant roles to play in potential problems or conflicts associated with patient privacy and confidentiality. Research objectives: The objective of the study is to determine the prevailing attitudes towards gossip and the patient privacy practices of nurses working in paediatric units. Research design: A descriptive and cross-sectional design was used. A Descriptive Characteristics Form, a Gossip and Rumour Attitude Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Further, patients’ age, gender, education status, the number of days they stayed in the hospital, the number of patients in their rooms, previous hospitalisations, and whether they were familiar with patient's rights also had no effect on their scores on privacy scale. However, in a study by Ceylan and Çetinkaya (2020), nurses who had a high education level, received training on patient privacy and who read the legal directives on patient rights were more attentive to or interested in patient privacy. In a study by Kim et al (2017), married nurses, nurses with university degree/higher education, charge nurses or higher‐level nurses gave more attention to behaviours aimed at protecting patient privacy.…”
Section: Discussionmentioning
confidence: 98%
“…Further, patients’ age, gender, education status, the number of days they stayed in the hospital, the number of patients in their rooms, previous hospitalisations, and whether they were familiar with patient's rights also had no effect on their scores on privacy scale. However, in a study by Ceylan and Çetinkaya (2020), nurses who had a high education level, received training on patient privacy and who read the legal directives on patient rights were more attentive to or interested in patient privacy. In a study by Kim et al (2017), married nurses, nurses with university degree/higher education, charge nurses or higher‐level nurses gave more attention to behaviours aimed at protecting patient privacy.…”
Section: Discussionmentioning
confidence: 98%
“…Medical ethics requires physicians who must be polite to patients, maintain patients’ privacy, and respect their beliefs and values [ 30 ]. Privacy is essential to create a sense of security in patients and physical and psychological support of patients [ 31 ]. In nursing and health care, patients have the right to make decisions independently, and respect for patients’ independence in health care has recently received special attention [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…30 Aktan et al indicated that 67 (41.6%) of the nurses in the study participated in training on privacy and patients' rights, and Ceylan and Çetinkaya highlighted that the nurses who received training on the subject had more privacy consciousness. 31,32 In a study conducted with nursing students, students emphasized that privacy training should be received to improve appropriate attitudes towards privacy, and more attention should be paid to privacy during training. 11 The results of our study support the literature.…”
Section: Discussionmentioning
confidence: 99%